Biochemical characterization of Campylobacter fetus lipopolysaccharides. - Moran, A P (1994)
Lipopolysaccharides (LPS) of five strains of the human and animal pathogen Campylobacter fetus were electrophoretically and chemically characterized. Analysis with sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that all the strains produced smooth-form LPS with O side chains of relatively constant chain length. Upon extraction, LPS partitioned into both the water and phenol phases of phenol-water extracts, which showed that two chemical species of LPS were present in each C. fetus strain. Constituents common to all the LPS, though differing in molar ratios, were L-rhamnose, L-fucose, D-mannose, D-glucose, D-galactose, L-glycero-D-manno-heptose, and D-glycero-D-manno-heptose. L-Acofriose (3-O-methyl-L-rhamnose) was present in only two of the C. fetus strains. On the basis of these differences, it was possible to distinguish between LPS from strains of different serotypes and biotypes. Furthermore, chemical analysis indicated that the phenol phase LPS had a lower level of substitution by certain neutral sugars than did water phase LPS. N-Acetylneuraminic (sialic) acid and D-galactosamine were present in all the C. fetus LPS. Constituents normally found in the core and lipid A regions of LPS, 3-deoxy-D-manno-2-octulosonic acid, D-glucosamine, ethanolamine and its phosphorylated derivatives, and fatty acids [14:0, 16:0 14:0(3-OH), and 16:0(3-OH)] were detected. Unlike Campylobacter jejuni, in which 2,3-diamino-2,3-dideoxy-D-glucose occurs as a constituent of the lipid A backbone, this amino sugar was absent from C. fetus LPS, indicating major structural differences in the lipid A's of these species.